Corrosion-Induced Failure Mechanisms in Bio-Nano Hybrid Coatings for Structural Applications - Maulidia Hendriani; Andoko Andoko; Riduwan Prasetya; Yahya Zakaria (Institut Teknologi Adhi Tama Surabaya, Indonesia, 2026)
This study examines the corrosion resistance performance and failure mechanisms of a hybrid coating system based on castor oil and nano-SiO₂ with three particle size variations (20 nm, 100 nm, and 500 nm) applied to ASTM A36 steel. We compared uncoated samples with three coating variants to evaluate the effect of nano-SiO₂ size on corrosion resistance and damage development. Coating resistance was tested using potentiodynamic polarization, FTIR analysis, corrosion morphology characterization, and coating thickness measurements. Compared to uncoated steel, the formulation with 100 nm nano-SiO₂ provided the greatest improvement, with a three-order decrease in corrosion current density (icorr = 1.33×10⁻⁸ A/cm²) and a shift in corrosion potential toward a more positive direction, accompanied by stable surface morphology and minimal chemical changes. This effectiveness is achieved through homogeneous particle dispersion, which produces a dense barrier structure and tortuous diffusion pathways without a significant increase in thickness. Failure mechanism analysis shows that small particle sizes (20 nm) trigger porous barrier breakdown due to nano-silica aggregation, while large particles (500 nm) cause coating cracking and localized pitting due to sedimentation and excessive thickness. In contrast, the 100 nm size stabilizes the passive film and suppresses pit initiation. These findings confirm that controlling the size and dispersion of nano-SiO₂ not only improves corrosion resistance but also determines the dominant failure pathway in coatings. This research contributes to the development of sustainable bio-nano coatings for structural applications by highlighting the importance of microstructural reinforcement and understanding failure mechanisms in designing high-resistance coating systems.